PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) BERBASIS INTERNET TERHADAP KEPUASAN PELANGGAN OYISAM CLOTHING MALANG - Rachmad Hidayat; Wahyu Budi Prakoso (Program Studi Manajemen STIE Kesuma Negara Blitar, 2018)
This research was conducted to find out a parcial or Simultaneously influence of Internet Based Customer Relationship Management (CRM) consisting of electronic Direct Mail (e-DM), interpersonal communication, preferential treatment, and reward to customer satisfaction at Oyisam Clothing Malang. The population in this research is 153 customers of Oyisam Clothing Malang. The sampling technique is simple random sampling and obtained a sample of 110 customers. Data collection techniques in this study using questionnaires. The results of this study show that sub-variables of the Internet-based Customer Relationship Management which includes electronic Direct Mail (e-DM), interpersonal communication (interpersonal communication), preferential treatment (preferential treatment), and rewards only preferential treatment that significantly and partially influence satisfaction Customer at Oyisam Clothing Malang. Keywords: e-DM, Interpersonal Communication, Preferential Treatment, Rewards, Customer Satisfaction